Prognostic Implications of Neutrophil Extracellular Traps in Coronary Thrombi of Patients with ST-Elevation Myocardial Infarction - Blasco, Ana; Coronado, María-José; Vela, Paula; Martín, Paloma; Solano, Jorge; Ramil, Elvira; Mesquida, Aína; Santos, Adrián; Cózar, Beatriz; Royuela, Ana; García, Diego; Camarzana, Susana; Parra, Carolina; Oteo, Juan F.; Goicolea, Javier; Bellas, Carmen (Thrombosis and Haemostasis, 2022)
Aims The mechanisms of coronary thrombosis can influence prognosis after ST-elevation myocardial infarction (STEMI) and allow for different treatment groups to be identified; an association between neutrophil extracellular traps (NETs) and unfavorable clinical outcomes has been suggested. Our aim was to determine the role played by NETs in coronary thrombosis and their influence on prognosis. The role of other histological features in prognosis and the association between NETs and bacteria in the coronary thrombi were also explored.Methods and Results We studied 406 patients with STEMI in which coronary thrombi were consecutively obtained by aspiration during angioplasty between 2012 and 2018. Analysis of NETs in paraffin-embedded thrombi was based on the colocalization of specific NET components by means of confocal microscopy. Immunohistochemistry stains were used to identify plaque fragments. Fluorescence in situ hybridization was used to detect bacteria.NETs were detected in 51% of the thrombi (NET density, median [interquartile range]: 25% [17–38%]). The median follow-up was 47 months (95% confidence interval [CI] 43–51); 105 (26%) patients experienced major adverse cardiac events (MACE). A significant association was found between the presence of NETs in coronary aspirates and the occurrence of MACE in the first 30 days after infarction (hazard ratio 2.82; 95% CI 1.26–6.35, p = 0.012), mainly due to cardiac deaths and stent thrombosis.Conclusion The presence of NETs in coronary thrombi was associated with a worse prognosis soon after STEMI. In some patients, NETs could be a treatment target and a feasible way to prevent reinfarction.
Keywords: ST-elevated myocardial infarction; coronary thrombi; neutrophil extracellular traps; atherosclerotic plaque; prognosis